Labor Market Discrimination Against Venezuelans in Peru: Evidence from a Correspondence Study - Torres, Javier (2024)
Through a correspondence study in Peru between July and September of 2021, we analyze the probability of Peruvian and Venezuelan applicants receiving callbacks to participate in a second stage of a job selection process. We studied the difference in the response rate by nationality, and tested potential mechanisms to reduce it, like holding a temporary residence permit (PTP) or having previous work experience in Peru. We find evidence of discrimination towards Venezuelan immigrants, as they have 4 percentage points less probability of receiving a callback than their Peruvian counterpart (a 43% difference with the control group rate). While previous work experience in Peru offsets the gap, holding a PTP does not attenuate employment discrimination.